Pengaruh Promo Diskon dan Gratis Ongkos Kirim di E-Commerce Shopee Terhadap Minat Beli Masyarakat di Kecamatan Beji Kota Depok - Armelia Putri; Desy Suryani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Shopee is one of the e-commerce companies that continues to increase in Indonesia. Shopee focuses more on the mobile platform so that people find it easier to search, shop and sell directly on their mobile phones. This study aims to analyze the